2017
DOI: 10.1177/2325967117734158
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Tibial Tuberosity–Trochlear Groove Offset Distance by Weightbearing Cone-Beam Computed Tomography Scan

Abstract: Background:Computed tomography (CT) scans are useful for objectively measuring bone alignment because they show bone detail particularly well, and these scans have been used extensively to assess patellar orientation. The tibial tubercle–trochlear groove (TT-TG) offset distance has been shown to be influenced by knee flexion and weightbearing, yet conventional CT scans are obtained with the subject relaxed, supine, and with the knee in full extension. A new cone-beam CT scanner has been designed to allow for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(75 reference statements)
2
9
0
Order By: Relevance
“…Tilt and congruence angles and TT-TG offset were all found significantly smaller under weight-bearing condition compared to conventional CT scan. Later, the same authors investigated the possible TT-TG offset variation between conventional CT and CBCT in a population of normal subjects [ 16 ] and concluded that also in this case CBCT scans result in significantly smaller values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tilt and congruence angles and TT-TG offset were all found significantly smaller under weight-bearing condition compared to conventional CT scan. Later, the same authors investigated the possible TT-TG offset variation between conventional CT and CBCT in a population of normal subjects [ 16 ] and concluded that also in this case CBCT scans result in significantly smaller values.…”
Section: Discussionmentioning
confidence: 99%
“…A p value of less than 0.05 was considered to be statistically significant; otherwise, the nonsignificance was indicated. The size of the patient sample analyzed in the present study was estimated by considering previous relevant literature [ 16 , 17 ], reporting the same acquisition technique as in the present study, and meets the criteria for achieving differences in measurements with 80% statistical power and a level of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Assessment and correction of patellar instability involve measurements of trochlear groove and position of the patella relative to other bones. 1,[4][5][6] Anatomical metrics might also provide risk stratification in anterior cruciate ligament injury. 3,[7][8][9] However, the repeatability and reliability of anatomical measurements are often challenged by factors associated with operator training and measurement techniques, 1,[10][11][12] diminishing their potential as quantitative biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed algorithm is applied to data of 24 subject volunteers acquired with a specialized extremity CBCT scanner. 23 Extremity CBCT systems provide the unique capability for weight-bearing three-dimensional (3-D) imaging of the knee 4,15,24 and foot. 15,24,25 Development of diagnostic applications of this new modality will benefit from improvements in the workflow, repeatability, and reliability of anatomical measurements that are anticipated with the automatic algorithm.…”
Section: Introductionmentioning
confidence: 99%